La despenalización del aborto por violación sexual en el Perú - Paucarchuco Gonzales, Frank James (2024)
The abortion debate is complex and multifaceted, encompassing not only legal and criminological aspects but also ethical and moral issues. Peru maintains a highly restrictive stance, allowing abortion only when the mother’s life or health is in danger. However, this prohibition contrasts with the reality of frequent clandestine abortions and scarce prosecution in our justice system. Given this situation, it is necessary to reopen the public debate, proposing the decriminalization of abortion in cases of sexual assault as a starting point. Taking these abortion cases as a starting point in this work responds to three arguments, namely, the special situation of women facing pregnancy, the compatibility with our legal framework, and the ineffectiveness of its current prohibition. In this way, the aim is to encourage general debate with a view to penal reform regarding abortion in our country.